Bridging and Conformational Control of Porphyrin Units through Non‐Traditional Rigid Scaffolds. Issue 11 (21st January 2020) - Grover, Nitika; Locke, Gemma M.; Flanagan, Keith J.; Beh, Michael H. R.; Thompson, Alison; Senge, Mathias O.
Abstract: Connecting two porphyrin units in a rigid linear fashion, without any undesired electron delocalization or communication between the chromophores, remains a synthetic challenge. Herein, a broad library of functionally diverse multi‐porphyrin arrays that incorporate the non‐traditional rigid linker groups cubane and bicyclo[1.1.1]pentane (BCP) is described. A robust, reliable, and versatile synthetic procedure was employed to access porphyrin‐cubane/BCP‐porphyrin arrays, representing the largest non‐polymeric structures available for cubane/BCP derivatives. These reactions demonstrate considerable substrate scope, from utilization of small phenyl moieties to large porphyrin rings, with varying lengths and different angles. To control conformational flexibility, amide bonds were introduced between the bridgehead carbon of BCP/cubane and the porphyrin rings. Through varying the orientation of the substituents around the amide bond of cubane/BCP, different intermolecular interactions were identified through single crystal X‐ray analysis. These studies revealed non‐covalent interactions that are the first‐of‐their‐kind including a unique iodine‐oxygen interaction between cubane units. These supramolecular architectures indicate the possibility to mimic a protein structure due to the sp 3 rigid scaffolds (BCP or cubane) that exhibit the essential conformational space for protein function while simultaneously providing amide bonds for molecular recognition. Abstract : Synthesis and characterization of novel porphyrin‐cubane/BCP arrays have been reported. The single crystal analysis revealed supramolecular 3D networks with combined and repetitive inter‐ and intramolecular H‐bonding interactions.